Inhaled Loxapine for the Management of Acute Agitation in Bipolar Disorder and Schizophrenia: Expert Review and Commentary in an Era of Change - Bruno Pacciardi; Alfredo Calcedo; Thomas Messer (Drugs in R&D, 2019)
Abstract Agitation is a common and costly phenomenon associated with a number of psychiatric conditions including schizophrenia and bipolar disorder. Early identification and prompt intervention to relieve the symptoms of agitation are essential to avoid symptomatic escalation and emergence of aggressive behaviour. Recent consensus guidelines emphasise the need for non-coercive management strategies to protect the therapeutic alliance between patients and their healthcare providers—an alliance that is critical for the effective management of chronic psychiatric conditions. Rapid symptom relief and de-escalation of agitation are necessary to avoid the costly and traumatic use of coercive techniques of physical restraint and seclusion, which require admission and prolonged hospitalisation. Inhaled loxapine is approved for the treatment of acute agitation in patients with schizophrenia or bipolar disorder. Clinical studies have confirmed the efficacy, rapid onset of action, and safety and tolerability of this agent in the psychiatric emergency and hospital settings. Emerging data have indicated the potential for inhaled loxapine as a self-administered agent for use in the community setting without the direct supervision of a healthcare professional. We discuss the evolving treatment paradigm and the place of inhaled medications for acutely agitated patients both within and outside the emergency and hospital setting.